Allotransplantation Is Associated With Exacerbation of CD8 T-Cell Senescence: The Particular Place of the Innate CD8 T-Cell Component - Daniel, Lauren; Tassery, Marion; Lateur, Clara; Thierry, Antoine; Herbelin, André; Gombert, Jean-Marc; Barbarin, Alice (Frontiers in Immunology, 2021)
Immunosenescence is a physiological process that is associated with changes in the immune system, particularly among CD8 T-cells. Recent studies have hypothesized that senescent CD8 T-cells are produced with chronologic age by chronic stimulation, leading to the acquisition of hallmarks of innate-like T-cells. While conventional CD8 T-cells are quite well characterized, CD8 T-cells sharing features of NK cells and memory CD8 T-cells, are a newly described immune cell population. They can be distinguished from conventional CD8 T-cells by their combined expression of panKIR/NKG2A and Eomesodermin (E), a unique phenotype closely associated with IFN- production in response to innate stimulation. Here, we first provided new evidence in favor of the innate character of panKIR/NKG2A(+) E(+) CD8 T-cells in normal subjects, documenting their position at an intermediate level in the innateness gradient in terms of both innate IFN- production and diminished mitochondrial mass. We also revealed that CD8 E(+) panKIR/NKG2A(+) T-cells, hereafter referred to as innate E(+) CD8 T-cells, exhibit increased senescent (CD27(-) CD28(-)) phenotype, compared to their conventional memory counterparts. Surprisingly, this phenomenon was not dependent on age. Given that inflammation related to chronic viral infection is known to induce NK-like marker expression and a senescence phenotype among CD8 T-cells, we hypothesized that innate E(+) CD8 T-cells will be preferentially associated with exacerbated cellular senescence in response to chronic alloantigen exposure or CMV infection. Accordingly, in a pilot cohort of stable kidney allotransplant recipients, we observed an increased frequency of the innate E(+) CD8 T-cell subset, together with an exacerbated senescent phenotype. Importantly, this phenotype cannot be explained by age alone, in clear contrast to their conventional memory counterparts. The senescent phenotype in CD8 T-cells was further increased in cytomegalovirus (CMV) positive serology transplant recipients, suggesting that transplantation and CMV, rather than aging by itself, may promote an exacerbated senescent phenotype of innate CD8 T-cells. In conclusion, we proposed that kidney transplantation, via the setting of inflammatory stimuli of alloantigen exposure and CMV infection, may exogenously age the CD8 T-cell compartment, especially its innate component. The physiopathological consequences of this change in the immune system remain to be elucidated.